2022
DOI: 10.1186/s12909-022-03217-w
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous online lecture may not be an effective method in teaching cardiovascular physiology during the COVID-19 pandemic

Abstract: Background Asynchronous online lecture has become a common teaching method in medical education, especially during the COVID-19 pandemic. However, the effectiveness and students’ attitudes towards this method under this special circumstance have not been exclusively studied. Hence, we aimed to evaluate these aspects of cardiovascular physiology teaching in an undergraduate medical curriculum. Methods We analysed and compared the academic achievemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
0
14
1
Order By: Relevance
“…More studies in the field of continuing medical education move along the same lines, emphasising the fact that e-learning was very important amid the pandemic, yet it will not replace traditional forms of medical education, but rather will complement them [ 57 , 58 ]. Nevertheless, mainly due to issues with the technological infrastructure and the lack of interactivity, it is also true that other experiences were not as satisfactory as expected and their participants preferred the traditional method [ 59 , 60 ]. To ensure success, technology requirements must be minimised and courses must be designed with a high level of interaction [ 61 ], as the intention of the participants, as well as the usefulness of the technology, are major factors that contribute to successful transitions to online learning [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…More studies in the field of continuing medical education move along the same lines, emphasising the fact that e-learning was very important amid the pandemic, yet it will not replace traditional forms of medical education, but rather will complement them [ 57 , 58 ]. Nevertheless, mainly due to issues with the technological infrastructure and the lack of interactivity, it is also true that other experiences were not as satisfactory as expected and their participants preferred the traditional method [ 59 , 60 ]. To ensure success, technology requirements must be minimised and courses must be designed with a high level of interaction [ 61 ], as the intention of the participants, as well as the usefulness of the technology, are major factors that contribute to successful transitions to online learning [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid onset of COVID-19, medical educators had to convert traditional face-to-face lectures to online lectures. Some medical educators found that students' academic achievement was stronger and student attitudes more positive when instructors used traditional face-to-face lecture format compared to online asynchronous lecture format 60 . However, this comparison involved asynchronous lecture format that did not follow best practices in instructional design but rather involved long videos of PowerPoint presentations with background narration 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Some medical educators found that students' academic achievement was stronger and student attitudes more positive when instructors used traditional face-to-face lecture format compared to online asynchronous lecture format 60 . However, this comparison involved asynchronous lecture format that did not follow best practices in instructional design but rather involved long videos of PowerPoint presentations with background narration 60 . Recent development of best practices in instructional design for didactic methods of teaching include more sophisticated multi-media presentation of content, and research tends to support positive outcomes for those approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of academic performance in this scoping varies greatly (see Table 2). There were six studies using GPA [18][19][20][21][22][23] ; nine studies using module scores [24][25][26][27][28][29][30][31][32] ; three studies implementing summative exam scores; [33][34][35] making use of practice/performance exams 2,36 ; two studies employing self-reported academic performance scores 37,38 ; and two studies applying laboratory examination scores. 39,40 Primary Outcome: Academic Performance in Medical Education Before and During the COVID-19 Pandemic…”
Section: Instruments To Measure Academic Performancementioning
confidence: 99%
“…Table 2 shows that 11 out of 24 publication reports on the academic performance before and during the COVID-19 pandemic. All of the studies reported comparative study before and during the COVID-19 pandemic based on learning methods (online methods vs traditional methods) within single medical school setting (n=11), 2,24,28,[31][32][33][35][36][37]39,40 with cohort as the research design option (n=10). 2,28,[31][32][33][35][36][37]39,40 Eleven studies were included in the evaluation of primary outcomes.…”
Section: Instruments To Measure Academic Performancementioning
confidence: 99%